STRIPED CATFISH (Pangasianodon hypophthalmus) (SAUVAGE, 1878) MOVEMENT AND GROWTH IN GAJAH MUNGKUR RESERVOIR, CENTRAL JAVA - Siti Nurul Aida; Agus Djoko Utomo (Indonesian Fisheries Research Journal, 2015)
Movement is an essential mechanism by which mobile animals acquire the resources necessary for the successful completion of their life-cycles. Striped catfish (Pangasianodon hypophthalmus) contributed about 384 tonnes or approximately 40,04% to the total fish production in Gajah Mungkur reservoir. Diversion of Keduang River, one of Gajah Mungkur important inlets, could affect the the movement of this fish. The objective of this research were to analyze data related to the movement patterns and growth of Pangasianodon hypophthalmus. Field works were conducted from March to December 2011 by tagging experiment of large fish with the PDS-Tags and the T Bar-Tags for the small ones. Fish samples used for the experiment were collected from fisherment catch in Gajah Mungkur reservoir. The tag numbers, the release time, and the fish size were noted before releasing the tagged fish were released. Fishermen who caught the tagged fish were advised to report the fish tag number, time of catching, and fish size. The results showed that the Pangasianodon hypophthalmus could moved as far as 200 m to 15 km in 3- 176 days. In the rainy season most of the catfish moved far into the inlet wiroko and Keduang, and some to the inlet Wuryantoro. Pangasianodon hypophthalmusin Gajah Mungkur Reservoir had growth equation of Lt= 99(1-e 0.762(t-0.15)), with the growth coeficient (K)= 0.762/year, t0=0.15 year, infinity length (L”)= 99 cm. Water diversion of Keduang river, one of Gajah Mungkur inlets, did not fully dried the River during dry season and affected striped catfish movement and growth.